KONDISI PSIKOSOSIAL-EKONOMI MANUSIA GEROBAK DI KOTA BEKASI PROVINSI JAWA BARAT - Dr. Epi Supiadi, M.Si; Annisa Aulia; Muhammad Ramdhan Firmansyah (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2022)
This study aims to reveal the characteristics of the manusia gerobak, the psychosocial and economic conditions of the manusia gerobak in the city of Bekasi. The study used a qualitative method with purposive sampling technique, resulting in 4 (four) manusia gerobak as the main informants and the supporting informants are Satpol PP officials and Social Service officials as well as the person in charge of the Bekasi City Shelter House. Data was collected by using interview, observation and documentation studies. The results showed that the biological conditions of all the informants were complete, healthy without a history of serious illness. The psychological condition of the informants is quite good, but they have negative emotions in the form of sadness and feelings of grief that come from their life journey. All of the informants have good relations with other manusia gerobak and their neighbors, except for two informa., who do not know the heads of the RT and RW. Relationships with family or relatives are quite varied. All informants have never received health and social assistance from the government. Spiritually, informants D and J are figures of manusia gerobak who are devout in their worship. The economic conditions of the informants include working time to scavenge waste ranging from 5-8 hours per day per person. Junk goods include plastic bottles, cardboard, wood, iron, cans and other used goods, with different selling prices depending on the prices set by the collectors. Daily income ranges from Rp. 25,000 – Rp. 60,000, with expenses to meet daily food needs, coffee, cigarettes and partly saved by Informants. In theory, the poverty experienced by the informants in terms of income is included in Primary poverty (primary/absolute poverty), namely poverty that can be described objectively as a lack of income earned to meet minimum needs.